2018
DOI: 10.1038/s41588-018-0203-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses identify 39 new susceptibility loci for diverticular disease

Abstract: Diverticular disease is common and has a high morbidity. Treatments are limited owing to the poor understanding of its pathophysiology. Here, to elucidate its etiology, we performed a genome-wide association study of diverticular disease (27,444 cases; 382,284 controls) from the UK Biobank and tested for replication in the Michigan Genomics Initiative (2,572 cases; 28,649 controls). We identified 42 loci associated with diverticular disease; 39 of these loci are novel. Using data-driven expression-prioritized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
99
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 68 publications
8
99
0
11
Order By: Relevance
“…Additional replication was observed for further eight loci in a combined meta-analysis of European colonoscopy cohorts with a European population cohort from Michigan (tables 2 and 3). Thirty-six out of 48 identified risk loci have been previously reported15 with genome-wide significant association (tables 2 and 3 and online supplementary table 4). All previously replicated risk loci for diverticular disease ( ARHGAP15 , FAM155A , COLQ) and ( GPR158, ABO, ANO1/FADD, ELN, BMPR1B, SLC35F3, SEM1/SHFM1 ) were identified both in the current GWAS and replication analyses with similar ORs to those reported by Sigurdsson et al 14 and Maguire et al 15 (table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional replication was observed for further eight loci in a combined meta-analysis of European colonoscopy cohorts with a European population cohort from Michigan (tables 2 and 3). Thirty-six out of 48 identified risk loci have been previously reported15 with genome-wide significant association (tables 2 and 3 and online supplementary table 4). All previously replicated risk loci for diverticular disease ( ARHGAP15 , FAM155A , COLQ) and ( GPR158, ABO, ANO1/FADD, ELN, BMPR1B, SLC35F3, SEM1/SHFM1 ) were identified both in the current GWAS and replication analyses with similar ORs to those reported by Sigurdsson et al 14 and Maguire et al 15 (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Overlap of risk loci to a previous GWAS by Maguire et al 15 and Sigurdsson et al 14 with the corresponding risk locus is indicated. Current GWAS risk loci are numbered descending by the p value in the discovery analysis.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations